Analysis of cooperative financial performance at the manunggal palm oil cooperative, Seresam Village, Seberida District, Indragiri Hulu Regency - Novriyani, Novriyani; Triyono, Aris; Rahayu, Tri (Institute of Computer Science (IOCS), 2025)
This study aims to analyze the Financial Performance of Cooperatives at the Manunggal Palm Oil Cooperative in 2018-2024. This type of research uses Primary Data and Secondary Data. The research method uses quantitative descriptive analysis to describe the financial performance of the Cooperative at the Manunggal Palm Oil Cooperative. Related to qualitative data in the form of descriptive data analyzed from items related to financial ratios. While quantitative data is taken from the financial statements listed in the Cooperative at the Manunggal Palm Oil Cooperative. The results of this study indicate that the financial performance of the Manunggal Palm Oil Cooperative based on the results of the liquidity ratio analysis using the Current Ratio fluctuates every year. This shows that the cooperative has a fairly high level of debt compared to the assets it owns. The financial performance of the Manunggal Palm Oil Cooperative based on the results of the solvency ratio analysis using the Debt to asset ratio where every year it always fluctuates. This shows that the cooperative has a fairly high level of debt compared to the assets it owns. The financial performance of the Manunggal Palm Oil Cooperative based on the results of the profitability ratio analysis using Return on Assets that fluctuates every year. This shows that the cooperative has a low ability to generate profits from its assets, because the cooperative is more concerned with improving the welfare of its members.